A new species of Cristarmadillidium from central Spain with remarks on Estenarmadillidium and Iberiarmadillidium (Isopoda: Oniscidea: Armadillidiidae) - Garcia, Lluc (Zootaxa, 2023)
The terrestrial isopod Cristarmadillidium cabanillasi sp. nov. (Isopoda: Oniscidea: Armadillidiidae) is described from Sierra Oeste and from the foothills of Sierra de Guadarrama (Madrid, Spain) in the Iberian Peninsula. The new species is the second of this genus to be discovered in the southwestern/central Iberian regions. In addition, morphological aspects of other endemic species of the related genera Estenarmadillidium and Iberiarmadillidium, are also discussed.